Effect of hysteresis on the stability of residual soil slope - Kristo, Christofer (2018)
Soil-water characteristic curve (SWCC) plays an important role in the application of unsaturated soil mechanics. Matric suction in an unsaturated soil changes with varying climatic conditions associated with cyclic drying and wetting conditions, resulting in hysteresis in the SWCC of the soil. The mechanical behaviour of soil under wetting is crucial for practical purposes since rainfall-induced slope failures occur during the wetting process. However, many slope stability analyses were carried out using drying SWCC. As a result, the factor of safety calculation may not represent the actual field condition. This report presents the effect of hysteresis in SWCC on the stability of unsaturated residual soil slopes from Bukit Timah Granite in Singapore. The study involved laboratory tests and numerical analyses. The laboratory tests comprised index property tests, SWCC tests, permeability test, and shear strength tests. Moreover, the numerical seepage and stability analyses considered the differences in pore-water pressure and water content variations under drying and wetting conditions. Each analysis was carried out on a slope subjected to dry and rainy periods under three different conditions: i) using only drying SWCC; ii) using only wetting SWCC; iii) using combined drying and wetting SWCCs. The results indicated that the factor of safety (FoS) variations obtained from the numerical analyses incorporating combined SWCC matched more closely those obtained by incorporating only wetting SWCC than those obtained by incorporating only drying SWCC, regardless of the wetting or drying processes that the soil experienced. Moreover, the numerical analyses under high rainfall intensity by incorporating only wetting SWCC gave a more conservative FoS as compared to those obtained by incorporating combined SWCC. Numerical analyses incorporating only drying SWCC gave the most conservative FoS regardless of rainfall intensity.